The Effect of Corn Particle Size on Starch Digestibility: In vitro - Ina Setiana; D.B. Utomo; Nahrowi Ramli (Buletin Ilmu Makanan Ternak, 2015)
Corn is the major component of broiler feed. The biggest component of corn is starch that is used as main energy source in broiler feed.  Corn particle size influence cost production of broiler feed, since decreasing grain particle to finer size requires greater energy use for grinding. The experiment was conducted to evaluate the effects of corn particle size on starch digestibility in vitro. The three particle sizes of corn were achieved by grinding corn in a hammer mill to pass through 3.25 mm (T1), 2 mm (T2), and 0.6 mm (T3) screen sizes.  Starch content was measured from 100 g samples of each treatment. Digestibility of the starch was measured using hydrolysis digestion. The starch was digested using amyloglucosidase enzyme and read after the digested sample were mixed with glucose oxidase and peroxidase (GOPOD) reagents. The results show that starch content of T1 was 66.50 %, T2 was 64.25 % and T3 was 66.40%. The digestibility of corn starch was higher for T3 compared with that of T1 and T2. It can be concluded that particle size improved starch digestibility of corn. Keywords: Corn, partdicle size, starch digestibility